A PMSG Wind Energy System Featuring Low-Voltage Ride-through via Mode-Shift Control - Rania A. Ibrahim; Nahla E. Zakzouk (Applied Sciences, 2022)
Low-voltage ride-through (LVRT) and grid support capability are becoming a necessity for grid-tied renewable energy sources to guarantee utility availability, quality and reliability. In this paper, a swap control scheme is proposed for grid-tied permanent magnet synchronous generator (PMSG) MW-level wind turbines. This scheme shifts system operation from maximum power point tracking (MPPT) mode to LVRT mode, during utility voltage sags. In this mode, the rectifier-boost machine-side converter overtakes DC-link voltage regulation independently of the grid-side converter. The latter attains grid synchronization by controlling active power injection into the grid to agree with grid current limits while supporting reactive power injection according to the sag depth. Thus grid code requirements are met and power converters safety is guaranteed. Moreover, the proposed approach uses the turbine-generator rotor inertia to store surplus energy during grid voltage dips; thus, there is no need for extra hardware storage devices. This proposed solution is applied on a converter topology featuring a minimal number of active switches, compared to the popular back-to-back converter topology. This adds to system compatibility, reducing its size, cost and switching losses. Simulation and experimental results are presented to validate the proposed approach during normal and LVRT operation.